APOLOGY OF THE RUSSIAN NATIONAL CURRENCY RATE (1992–2015) - Vladimir P. Semenov; Yuriy P. Soloviev (Вестник Российского экономического университета имени Г. В. Плеханова)
During 25 years of existence and development of market economy in Russia the algorithm of forming the currency rate, which is adequate to economic situation in the country has not been designed. The ruble rate to world reserve currencies controlled by Russian administration always has certain signs of voluntarism and is fixed without due regard to the ruble inflation rate. Finally, it led to tough currency and finance crises (1998, 2008, 2014). The article identifies factors affecting formation of currency rate of the ruble and investigates policy of monetary powers for the last 25 years. Forecasts of currency rate of the ruble are offered.